Flange union at nanoscale: fabrication and formation mechanism. Issue 17 (31st March 2020) - Zhong, Shengliang; Zou, Honghong; Ji, Yanhua; Zeng, Chenghui; Wang, Lei; Chen, Yanhong; Xu, Hualan
Abstract : Coordination polymer superstructures connected by a flange union with a good geometry were fabricated. Assembly, disassembly and reassembly process happened during the formation. Abstract : In this study, for the first time, yttrium-based coordination polymer (YCP) superstructures connected by a flange union with a good geometry were fabricated via a facile hydrothermal method. The formation mechanism was investigated in detail. An assembly, disassembly and reassembly process happened during the reaction process. Furthermore, the doping concentration and reaction temperature were found to have great effects on the morphology of the product. Employing this method, lanthanide (Ln)-based CP (LnCP) particles with complex structures were also prepared. The YCP superstructures were tested for drug delivery. The drug encapsulation rate (EE%) and drug loading rate (DLC%) were 87% and 57%, respectively. The present study provides some guidelines for the preparation of CPs with complex structures and the fabrication of CP nanodevices.